Djursjukskötarens roll i rehabiliteringen av inneliggande patienter på hästsjukhus - Johansson, Maria (2014)
Veterinary hospital care and advanced veterinary services are rapidly growing industries. As of January 1, 2010, veterinary nursing became a licensed vocation, the title of veterinary nurse became protected, and the act regulating competence among the professions of the veterinary field was extended. These changes, along with increased demands and expectations from owners, have given rise to greater demands on the staff's qualifications and have increased the need for well-educated staff with expertise in several different areas.